Kebersihan dan Kesehatan Lingkungan menurut Hadis - Aulia, Afianda Ghinaya (Jurnal Riset Agama, 2021)
This study aims to discuss the hadith about environmental hygiene and health and sanctions for environmental destroyers. This research method is qualitative through literature study with content analysis. The result and discussion of this study include the definition of Environmental hygiene and health, how the hadith about environmental hygiene dan health and sanction for environmental destroyers are very important things to do. The Environment is one of the prerequisites for the survival and life of mankind with land, water and air as the main components. There are several hadith that show the recommendation to clean the Environmental from dirt, so it is not appropriate for a believer to underestimate it. This is what the Prophet Muhammad Saw, his companions and the salaf scholars practiced. Perpetrators of Environmental destruction can be categorized as criminal acts and there is a threat to the.Â Â